PENGARUH PENAMBAHAN IKAN KEMBUNG (Rastrelliger kanagurta L.) DALAM PAKAN TERHADAP PENURUNAN KADAR TOTAL KOLESTEROL DALAM DARAH MENCIT (Mus musculus) JANTAN YANG HIPERKOLESTEROLEMIA - Mila Fitriana; Rudi Kartika; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2017)
Fish is a source of omega-3 which is good for our health. This study used one type of fish that contains high omega-3 (Rastrelliger kanagurta L.). This fish as s feed against the decrease in total blood cholesterol levels in mice (Mus musculus) are hypercholesterolemia. There are 5 treatments used in this study, i.e positive control, negative control, and mice which given the addition of bloated fish on standard feed with 3 different treatments L1 (2:1), L2 (2:2), L3 (1:2). Parameters measurement of total cholesterol level of mice is using CHOD-PAP method. The principle used in determining the total cholesterol level of mice blood cholesterol obtained is (+) 142 ; (-) 86 ; (L1) 108 ; (L2) 87 ; (L3) 74 .The result of this study showed that bloated fish (Rastrelliger kanagurta L.) used to reduce the total blood cholesterol level of male hypercholesterolemia mice (Mus musculus). Keywords : total cholesterol, bloated fish, omega-3, Hypercholesterolemia, male mice